2013
DOI: 10.4049/jimmunol.1202120
|View full text |Cite
|
Sign up to set email alerts
|

NK Cell Tolerance of Self-Specific Activating Receptor KIR2DS1 in Individuals with Cognate HLA-C2 Ligand

Abstract: NK cells are regulated by inhibiting and activating cell surface receptors. Most inhibitory receptors recognize MHC-class I antigens, and protect healthy cells from NK cell-mediated auto-aggression. However, certain activating receptors, including the human killer cell Ig-like receptor (KIR) 2DS1, also recognize MHC-class I. This raises the question of how NK cells expressing such activating receptors are tolerized to host tissues. We investigated whether the presence of HLA-C2, the cognate ligand for 2DS1, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 52 publications
4
59
2
1
Order By: Relevance
“…The HLA-C1 or HLA-C2 status of the mother is also important as KIR2DS1sp dNK from C1/C1 donors respond better to HLA-C2 + targets than those from C2/C1 heterozygotes. This contrasts with pbNK, where tuning down of KIR2DS1 responses to HLA-C2 was observed only in HLA-C2 homozygotes (25,26,29,30). The rheostat model of NK education proposes that NK cell function is "tuned" by interactions between inhibitory and activating receptors on the cell and their ligands during NK development, and quantity of MHC also affects NK cell responsiveness (48,49).…”
Section: Figurecontrasting
confidence: 46%
“…The HLA-C1 or HLA-C2 status of the mother is also important as KIR2DS1sp dNK from C1/C1 donors respond better to HLA-C2 + targets than those from C2/C1 heterozygotes. This contrasts with pbNK, where tuning down of KIR2DS1 responses to HLA-C2 was observed only in HLA-C2 homozygotes (25,26,29,30). The rheostat model of NK education proposes that NK cell function is "tuned" by interactions between inhibitory and activating receptors on the cell and their ligands during NK development, and quantity of MHC also affects NK cell responsiveness (48,49).…”
Section: Figurecontrasting
confidence: 46%
“…This combination has been reported to be associated with increased tolerance of KIR2DS1 expressing NK cells. 16,21 Several genetic population studies have analyzed the relationship between maternal KIR profile and susceptibility to various pregnancy-related disorders including recurrent pregnancy loss, 32-36 preeclampsia 29,30,44 , and intrauterine fetal growth restriction. 31 Similar to preeclampsia, it was shown that maternal KIR AA genotype in combination with the presence of HLA-C2 in partners is a risk factor for RPL.…”
Section: Discussionmentioning
confidence: 99%
“…18 Coexpression of activating KIR2DS1 and its ligand, HLA-C2, implicates hyporesponsiveness of KIR2DS1-positive NK cells toward HLA-C2 targets, known as NK cell education. 16,[19][20][21] The associations between certain KIRs along with the presence/absence of their cognate HLA-C ligands and some infectious diseases, autoimmune diseases, and cancer have been accumulated. [22][23][24][25][26][27][28] In case of pregnancy, when maternal dNK cells interact with HLA-C on fetal-derived trophoblasts, the extent of the NK cell response may be determined by both the availability of corresponding KIR ligands on trophoblasts as well as by the maternal HLA-C background responsible for NK cell licensing and education.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the inhibitory KIRs, the ligands for many activating KIRs are largely unknown. KIR2DS1 has been shown to interact with HLA-C2 alleles, [65][66][67] whereas KIR2DS2 was recently shown to recognize HLA-A*11. 68 The frequencies of KIR alleles vary from population to population, but most individuals have inhibitory KIRs specific for HLA-C1, -C2 or -Bw4 alleles.…”
Section: Cd56mentioning
confidence: 99%
“…Activating KIRs recognize stress molecules and possibly also HLA molecules or modified HLA molecules, but only the specificity of KIR2DS1 for HLA-C2 alleles has been firmly established. [65][66][67] Although all individuals carry the genes for inhibitory KIR receptors-which indicates that they are necessary for NK cell function-there is striking heterogeneity in the number of inherited activating KIR genes in the normal population. 69 Based on the number and distribution of activating KIR genes, individuals can be considered to have 2 broad KIR haplotypes.…”
Section: Cd56mentioning
confidence: 99%